2017
DOI: 10.1007/978-3-319-48933-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductivity in Materials Research

Abstract: Electrical transport through materials is a large and complex field, and in this chapter we cover only a few aspects that are relevant to practical applications. We start with a review of the semi-classical approach that leads to the concepts of drift velocity, mobility and conductivity, from which Matthiessen's Rule is derived. A more general approach based on the Boltzmann transport equation is also discussed. We review the conductivity of metals and include a useful collection of experimental data. The cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…They include the pseudotwin boundary in the (112) planes, separating lamellae of CuInS 2 that are rotated 180° against their neighbors; 1/6 ⟨1̅1̅1⟩ partial dislocations that accommodate a bond mismatch at the periphery of the embedded interphase layers; and a one-bond offset with respect to the bulk, of lattice planes that terminate at interphase layers. Typically, such planar and line defects cause electronic defects, and indeed many point defects have been postulated for CuInS 2 . , While no specific electronic defect has been identified in this study, the observed photoconductivity exponent of 0.54 suggests that electronic defect levels do exist in the energy band gap, with a density of defect states decaying away from the band edges. , For a comprehensive overview of point defects in a chalcopyrite, the reader is referred to the discussion of CuInSe 2 by Zhang et al…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…They include the pseudotwin boundary in the (112) planes, separating lamellae of CuInS 2 that are rotated 180° against their neighbors; 1/6 ⟨1̅1̅1⟩ partial dislocations that accommodate a bond mismatch at the periphery of the embedded interphase layers; and a one-bond offset with respect to the bulk, of lattice planes that terminate at interphase layers. Typically, such planar and line defects cause electronic defects, and indeed many point defects have been postulated for CuInS 2 . , While no specific electronic defect has been identified in this study, the observed photoconductivity exponent of 0.54 suggests that electronic defect levels do exist in the energy band gap, with a density of defect states decaying away from the band edges. , For a comprehensive overview of point defects in a chalcopyrite, the reader is referred to the discussion of CuInSe 2 by Zhang et al…”
Section: Discussionmentioning
confidence: 68%
“…45,55−61 While no specific electronic defect has been identified in this study, the observed photoconductivity exponent of 0.54 suggests that electronic defect levels do exist in the energy band gap, with a density of defect states decaying away from the band edges. 53,62 For a comprehensive overview of point defects in a chalcopyrite, the reader is referred to the discussion of CuInSe 2 by Zhang et al 45 The fully embedded interphase (Figure S4) demonstrates that pseudotwin boundaries do exist in the absence of interphases. This suggests that at least some, and possibly all, of the interphases did form following the growth of a nonstoichiometric crystal.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(a) is the steady-state conductivity under illumination, and figure 3(b) the ambipolar diffusion length obtained from SSPG measurements. Figure 3(b) includes the statistical errors obtained for L amb when the SSPG experimental data are fitted with equation (12). When the relative error is calculated, the trend is clear: the error increases when the generation rate increases and when the temperature decreases.…”
Section: Experimental Methodsmentioning
confidence: 97%
“…Several experimental methods have been developed to obtain the DOS within the mobility gap of amorphous semiconductors exhibiting photoconductivity. These methods can be classified into two broad categories: (i) methods where the experimental data are used directly to determine the DOS, based on an approximate reconstruction formula derived from a theoretical analysis of the experiment [11,12]; and (ii) methods where an initial DOS described by several parameters is proposed, obtaining the parameter values from a fit of the experimental data with a formula provided by the theoretical description of the experiment [6,13]. The main drawback of the methods belonging to the first category is that several approximations are needed to obtain an analytical formula for the DOS, which is usually valid over only a limited energy range.…”
Section: Introductionmentioning
confidence: 99%
“…The photoconductive polymers are a class of functional solidstate materials which, can trigger significant photocurrent generation by the absorption of photons and have attracted substantial attention due to their successful application in optical and electronic devices. [1][2][3][4][5] The design of efficient photoconductive polymers requires electron-rich intrinsic semiconductive and photoconductive building blocks with the modular assembly that allows the formation of multiple conducting pathways (through-bond and through-space charge transport). 6 The through-bond charge transport can be reached with extended π-conjugated polymer with efficient charge delocalization whereas through space transport requires to form short long-range p-orbital overlap in the stacking direction.…”
mentioning
confidence: 99%